A Rainy day - Schaefer, Lola M. (Mankato, Minnesota : Capstone Press, 2000)
Simple text and photographs depict a rainy day, including the formation of rain and the actions of the people out in it.
Includes bibliographical references and index.
Keywords: Rain and rainfall -- Juvenile literature; Raindrops -- Juvenile literature